Genetic characterization of Moniezia species in Senegal and Ethiopia. Issue 5 (October 2015) - Diop, Gora; Yanagida, Tetsuya; Hailemariam, Zerihun; Menkir, Sissay; Nakao, Minoru; Sako, Yasuhito; Ba, Cheikh Tidiane; Ito, Akira
Abstract Genetic diversity of Moniezia spp. from domestic ruminants in Senegal and Ethiopia was investigated based on the nucleotide sequences of mitochondrial cytochrome c oxidase subunit 1 (cox1) and nuclear small subunit ribosomal RNA gene (SSU rDNA). A total of 64 adult tapeworms were collected from sheep, goat and cattle, and the tapeworms from cattle were all morphologically identified as Moniezia benedeni. On the other hand, the tapeworms obtained from sheep and goat were identified as Moniezia expansa or could not be identified because of the lack of diagnostic morphologic character, i.e. interproglottidal glands (IPGs). Phylogenetic analysis based on cox1 gene sequences revealed that the worms from sheep/goat and cattle formed distinct clades, and three mitochondrial lineages were confirmed within the sheep/goat tapeworms. The maximum pairwise divergences among the three mitochondrial linages were about 3% in cox1 and 0.1% in SSU rDNA, while that between the worms from sheep/goat and cattle reached 13% in cox1 and 2.7% in SSU rDNA. All of the three mitochondrial lineages contained tapeworms morphologically identified as M. expansa, and the tapeworms without IPGs were confirmed in one of the three lineages, indicating the tapeworms without IPGs were also M. expansa.